Financial Inclusion through Technological Advancements in Banking Institutions: An Analytical Review - Rahman, Abdul (Advances: Jurnal Ekonomi & Bisnis, 2024)
The purpose of this analytical review is to explore the nexus between technological advancements in banking institutions and their impact on financial inclusion. The research design and methodology involve an extensive literature review and analysis of relevant studies from various sources. Findings reveal that technological innovations, including mobile banking apps, digital payment platforms, artificial intelligence, and blockchain technology, have significantly contributed to enhancing financial inclusion by improving accessibility, reducing transaction costs, and empowering marginalized communities and small businesses. The discussion highlights the transformative effects of fintech on financial services, emphasizing the role of peer-to-peer lending, digital wallets, and blockchain-based solutions in democratizing access to finance and promoting financial literacy. The implications of these findings suggest the need for collaborative efforts between public and private sectors to leverage technology effectively, enhance digital literacy, address data privacy concerns, and develop inclusive regulatory frameworks. This holistic approach is crucial for fostering inclusive and sustainable financial systems globally, benefiting individuals and communities across diverse socio-economic backgrounds.